Pengaruh Peran Perdagangan Internasional Terhadap Strategi Pembangunan Ekonomi Indonesia Di Era Global Tahun 2024 - Tri Ayu Fadilah; Elisabeth Tamara Ratu Hutauruk; Irna Della Br Ginting; Nataline Simanjuntak; Evi Syuriani Harahap (Sharing: Journal of Islamic Economics Management and Business, 2026)
International trade plays a crucial role in supporting economic development amidst increasing global economic integration. Export and import activities contribute to economic growth through market expansion, increased foreign exchange earnings, technology transfer, and support for national production capacity. This study aims to analyze the influence of international trade on Indonesia's economic development strategy in the global era in 2024. The study uses a quantitative approach utilizing secondary data in the form of Indonesian export and import values ​​obtained from official statistical publications and various related scientific sources. The analysis was conducted using quantitative descriptive methods to examine the contribution of international trade to national economic development. The results show that exports contribute positively through increasing foreign exchange earnings, creating jobs, and strengthening the competitiveness of domestic products in the international market. Meanwhile, imports support economic activity by providing raw materials, capital goods, and technology needed in the production process. These findings confirm that international trade remains a crucial component of Indonesia's sustainable economic development strategy.